2016
DOI: 10.1017/jmo.2016.59
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of transformational leadership and job satisfaction: The roles of personality traits and psychological empowerment

Abstract: Through two studies, this paper investigates the moderating effects of personality traits (i.e., extraversion, conscientiousness, agreeableness and neuroticism) and the mediating effect of psychological empowerment on the relationship between perceived transformational leadership and job satisfaction. Study 1 searches whether personality traits moderate the effects of perceived transformational leadership on followers' job satisfaction. Using a sample of 221 R&D employees employed by information technology org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
4

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 116 publications
(188 reference statements)
2
31
0
4
Order By: Relevance
“…Therefore, it can be proposed that the transformational leadership style is a possible predictor of psychological empowerment. Past studies proclaim a significantly positive nexus between transformational leadership and psychological empowerment [47,56,57]. Therefore, we hypothesize that: Hypothesis 2 (H2).…”
Section: Transformational Leadership and Psychological Empowermentmentioning
confidence: 89%
See 1 more Smart Citation
“…Therefore, it can be proposed that the transformational leadership style is a possible predictor of psychological empowerment. Past studies proclaim a significantly positive nexus between transformational leadership and psychological empowerment [47,56,57]. Therefore, we hypothesize that: Hypothesis 2 (H2).…”
Section: Transformational Leadership and Psychological Empowermentmentioning
confidence: 89%
“…The concept of employee empowerment has been extensively studied during the last two decades in different settings and contexts, such as information technology organizations and academics [47], social workers [48], banking managers [49], public welfare caseworkers [50], manufacturing firms [51], hotel staff [52] and nurses [11]. Spreitzer [53] defined psychological empowerment as "increased intrinsic task motivation manifested in a set of four cognitions reflecting an individual's orientation to his or her work role: competence, impact, meaning, and self-determination" (p. 1443).…”
Section: Transformational Leadership and Psychological Empowermentmentioning
confidence: 99%
“…It is demonstrated that the employees who receive organizational support show more satisfaction toward their job and have lower turnover rate [49]. A recent study demonstrated that psychological empowerment works as an essential force that intervenes in the association between POS and job satisfaction [8]. Many researches on social exchange [2] and the norms of reciprocity [37] emphasize that employees feel obligated and are ready to assist their coworkers as well as their employers.…”
Section: Mediating Role Of Psychological Empowermentmentioning
confidence: 99%
“…Psychologically empowered employee not only exerts efforts in workplace but also wish to stay in the organization. Numerous studies have reported consequence of empowerment; job satisfaction have been acknowledged often (Amundsen & Martinsen, 2015;Aydogmus et al, 2018;Humborstad & Perry, 2011). Efficiently implementing empowerment among employee depends on leadership, which results in enhancement of employee involvement in work and giving autonomy.…”
Section: Psychological Empowermentmentioning
confidence: 99%
“…To survive and progress in such competitive environment, more than ever, these organizations want to keep their employees to be contented and satisfied. Many studies recommend the "perfect worker" is the one who is highly satisfied, who has the will to go an extra mile to help the organization achieve its goal (Aydogmus, Camgoz, Ergeneli, & Ekmekci, 2018). It has been well established that satisfied personnel are more likely to be committed to their organization (Humborstad & Perry, 2011), have higher level of job performance (Yang & Hwang, 2014), lower levels of turnover (Lu, Zhao, & While, 2019).…”
Section: Introductionmentioning
confidence: 99%